Analysis of Basic Sectors and Economic Dynamics of Makassar City toward South Sulawesi Province (2020–2024) - Rayhan, Yohan (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the structure and dynamics of Makassar City's economy in comparison to South Sulawesi Province over the 2020–2024 period. Using a sectoral quantitative approach, the study applies four regional economic analysis tools: Location Quotient (LQ), Dynamic Location Quotient (DLQ), Klassen Typology, and Shift Share Analysis (SSA). The results indicate that several sectors in Makassar, such as Wholesale and Retail Trade, Manufacturing, and Information and Communication, are base sectors with high average LQ values. However, DLQ analysis reveals that only the Accommodation and Food Services sector and the Public Administration sector show promising prospects. Klassen Typology categorizes most sectors as “developed but depressed,” indicating strong contributions with underwhelming growth. Shift Share analysis reveals that while many sectors grew positively during the study period, much of this growth is attributed to national trends and sectoral structures, rather than local competitive advantages. Only a few sectors, such as Accommodation and Food Services, Health, and Transportation, exhibit positive competitive shifts. These findings underscore the need for Makassar's development policy to strengthen internal sectoral competitiveness for more sustainable regional growth.